Tensile properties of additively manufactured polyetherimide parts - Gajdoš, Ivan; Spišák, Emil; Jachowicz, Tomasz; Garbacz, Tomasz (Advances in Mechanical and Materials Engineering, 2016)
This paper presents the results of a study of evaluating the influence of path generation strategy on tensile properties of samples made by additive manufacturing technology FDM (Fused Deposition Modeling). Several scientific studies were focused on the influence of path generation strategy on mechanical properties of deposited material. ABS and PLA are the most investigated materials used in FDM. This paper is aimed to determine the influence of selected path generation strategies on tensile strength of parts fabricated with ULTEM 9085 thermoplastic. The results obtained in experiments confirmed that proposed path generation strategy allowed to increase tensile strength by 25% compared to a situation when the samples were fabricated with default path generation setting.